Study of isotopic exchange reaction of iodine in neutral aqueous solutions of iodide-iodate system by radiotracer technique - Ram K.D.; Tripathi R. (My University, 2025)
The isotopic exchange reaction of iodine in neutral aqueous solutions of iodide and iodate ions at 250°C is found to be second order, and first order with respect to each of the reactants. This indicates the presence of an induction period of 0.5-10 h depending upon the concentration of the reactants and temperature. The addition of neutral ionic salts, e.g. NaCl, NaNO3 and Na2SO4, in the reaction mixture showed a slight catalytic effect on the exchange rate. Further, the kinetic salt effect indicated the involvement of reacting species of similar charge in the rate determining step. The activation energy in the neutral aqueous solutions of iodide and iodate ions is found to be 155 ± 5 kJ mol-1, which decreases in the presence of NaCl (128 ± 5 kJ mol-1), NaNO3 (134 ± 5 kJ mol-1) and Na2SO4 (116 ± 5 kJ mol-1). The activation parameters, viz. free energy of activation, enthalpy of activation and entropy of activation, were also calculated. Based on these results, an association-dissociation mechanism is proposed for the exchange reaction in neutral aqueous medium. © 1989.